Everything's good : cozy classics you'll cook always & forever - Chapman, Toni (Clarkson Potter/Publishers, 2025)
"Find joy in the kitchen with 100 recipes for nostalgic, flavorful comfort food from the creator of The Moody Foody Toni Chapman is a social media star who shares easy recipes for the homey classics you crave. Toni grew up in a family that loves to cook, and her homestyle cooking speaks to the beautiful intersectionality of food and family. Her dishes are inspired by the multicultural community she grew up in, mixing her Puerto Rican, Caribbean, and African American heritage with flavors from all over the globe. The recipes she shares in Everything's Good are approachable and weeknight friendly, dialed in with her relentless attention to detail and brought to life by her bold and flavorful style. In Everything's Good, Toni shares a treasure trove of brand-new recipes (and some viral favorites) with tips and tricks to set you up for success. Toni's dishes are soulful and cozy-several recipes have been passed down from her family like Pollo Guisado; some are inspired by the Southern staples she grew up eating, such as One-Pot Dirty Rice with Chicken; and while others are Toni's takes on the classics, like Cod Scampi with Coconut Rice. Her irresistible, foolproof recipes include: Take Time for Breakfast: Crispy and Spiced Breakfast Potatoes; Strawberries & Cream Croissant Bake; Freezer Door Breakfast Sandos Start with Something Special: Spinach, Crab, and Artichoke-Stuffed Shrimp; Sofrito Chicken Empanadas; Chopped Cheese Sliders Soulful Soups: Marry-Me Soup; Pozole Verde; Zuppa Toscano Takeout Favorites: Pork Fried Rice; Halal Cart Bowls; Crunchy Crispy Fried Chicken Family Style: Creamy Mac and Cheese; Cajun Butter Turkey; Pernil (Puerto Rican Roast Pork) For Toni, food is a source of solace. Everything's Good is a reminder that no matter what life throws your way, you can find comfort in preparing and sharing a delicious meal"--